Exploring the potential of assessment efficacy in sports coaching - A Commentary - Carless, D. (International Journal of Sports Science and Coaching, 2012)
Assessment is a thorny issue. In recent years, many of us have witnessed - or been participants in - moves towards more widespread and frequent formalised assessment of not only our professional lives, but our personal lives too. This has taken the form of, for example, increased formal academic testing of schoolchildren, expanding initial and ongoing accreditation across many professions and vocations, and widespread monitoring as part of routine public healthcare. Some argue that increased use of formalised assessment is necessary to ensure accountability, efficiency, cost-effectiveness, maintenance or improvement of standards, or perhaps to identify `talent`. This argument currently looms large in public discourse and political rhetoric. Others counter that excessive formal assessment distracts from the core processes of learning and development, encourages an outcome focus (leading to a `teach to the test` ethos), creates unnecessary and unhealthy pressure and stress, and ultimately results in an acquisitive rather than inquisitive learning culture where education comes to be more about satisfying external `benchmarks` than achieving personal development or transformation. This counter argument is often marginalised - whispered in conversations between concerned practitioners or cautiously broached by social scientists in academic publications.